Insights from LLIN post-distribution monitoring surveys in the malaria transmission foci of the Dominican Republic: implications for quantification and distribution strategies - Gilda Ventura; María Yinet Santos Félix; Natalia Tejada Bueno; Nicole Michelén Ströfer; Jose Luis Cruz Raposo; Ángel Solís; Rafael German Barrios Parra; Lucía Fernández Montoya (Malaria Journal)
Abstract Background Long-lasting insecticidal nets (LLINs) have been distributed and installed in the Dominican Republic since 2008, and they remain the main vector control intervention used to pursue malaria elimination in the country. However, LLIN performance remains unclear due to a lack of monitoring over the past decade. Methods A cross-sectional household survey was conducted to monitor LLIN coverage, access, use, physical integrity, washing and drying practices, and the time people go to bed and wake up in the two main malaria foci of the country: Azua (4–6 months post-distribution and installation) and San Juan (one year post-distribution and installation). Results The percentage of sleeping spaces that could be covered with a LLIN given the LLINs present in the household was 64% in Azua and 63% in San Juan; with any net, coverage was 75% in Azua and 80% in San Juan. Reported LLIN retention was 88.4% in Azua and 80.9% in San Juan. The percentage of people who had access to sleeping under an LLIN was 58.8% in Azua and 65.4% in San Juan. Among people with LLIN access (people with enough LLINs to cover all sleeping spaces in their household), use was 48.8% in Azua and 75% in San Juan; and overall, LLINs use was 32.3% in Azua and 50.5% in San Juan. Most LLINs remained in serviceable physical condition (Azua: 96.4%, San Juan: 88.9%) but those with holes were not repaired. Most LLINs were washed with aggressive products (Azua: 65%, San Juan: 86%), at a frequency that suggests they will be washed more than twenty times in three years (Azua: 52%, San Juan: 73%), and dried under the sun (Azua: 75%, San Juan: 90%). Conclusion Poor washing and drying practices are prevalent in both areas, low LLIN use was observed in Azua and some LLIN coverage gaps were measured in both foci. Urgent behavioural change strategies are needed to improve LLIN care in both foci and to increase LLIN use in Azua, alongside revisions to LLIN quantification methods to ensure full coverage of all sleeping spaces in use during installation. Heterogeneities in LLINs use across foci suggest the need for monitoring use in each distribution area to identify individual gaps and promptly address them.